Estrategia didáctica mediada por un Objeto Virtual de Aprendizaje (OVA), para el fortalecimiento de las competencias digitales en los docentes de la Institución Educativa General Santander (2023)
This research addresses an educational problem related to the scarce development of digital competencies limiting the efficiency of academic of the teacher’s processes of the General Santander Educational Institution of the city of Monteria, Cordoba. Consequently, the implementation of a didactic strategy mediated by a Virtual Learning Object (VLO) is proposed. The purpose of this is to strengthen competencies in digital management tools oriented to academic processes, as established by the Ministry of National Education (MEN), through guidelines for the professional development of teachers in ICT competencies. This study is subject to a qualitative approach with an action research design. Thus, it seeks the construction of meaningful learning through practical situations where the participation and digital experience of the population have been working during the entire application process. In this work, an intervention is carried out in five phases ranging from the dissemination and application of a diagnostic test, through the design of the OVA based on the results of the aforementioned test and MEN guidelines. The pedagogical intervention and application of an evaluation test to identify whether the purpose of the project was fulfilled. Subsequently, the results of the diagnostic test and the evaluation test were contrasted, where it became evident that the study population had a substantial improvement concerning the use and implementation of digital educational tools in their context.